The preference of insect predators on several types of flowering plants as insectary plant in cayenne pepper fields - KIRANA FADHILAH; BAMBANG TRI RAHARDJO; MOCHAMMAD SYAMSUL HADI (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Fadhilah K, Rahardjo BT, Hadi MS. 2023. The preference of insect predators on several types of flowering plants as insectary plant in cayenne pepper fields. Biodiversitas 24: 6177-6183. Cayenne pepper (Capsicum frutescens L.) is a popular commodity yet often suffers from reduced yields due to pest attacks. Therefore, growing this plant requires environmentally friendly management. One of the measures is using the baby blue eyes (Nemophila menziesii) plant. Baby blue eyes are promising insectary plants since they attract predatory insects. This study, which was conducted in Kasin Village, Karangploso, Malang, from March to June 2023, aimed to explore the predatory insects' diversities and preferences in cayenne pepper fields by comparing baby blue eyes as insectary plants with common zinnias and marigolds. The research comprised four treatments: P1. Control; P2. Cayenne peppers + baby blue eyes; P3. Cayenne peppers + common zinnias (Zinnia elegans); and P4. Cayenne peppers + marigolds (Tagetes erecta). The study revealed lady beetle Coccinella transversalis, Menochilus sexmaculatus, and big-eyed bug Geocoris sp. as the most abundant predatory insects with increasing populations across the treatments. The highest predator insect diversity was found in the Cayenne pepper + baby blue eyes (P2) treatment. In conclusion, baby blue eyes attract more predatory insects in cayenne pepper fields than other insectary plants, making them valuable alternatives besides common zinnias and marigolds. These findings provide a reference for future studies to promote baby blue eyes as insectary plants for farmers.